Hubungan Pola Makan Dan Aktivitas Fisik Dengan Kejadian Overweight Pada Remaja - Putri Andrini; Aisah; Ariyanto (STIKes MERCUBAKTIJAYA, 2023)
Excess weight in adolescents is caused by energy intake that exceeds needs or insufficient energy consumption and is related to a history of eating habits and the frequency of intake of high-calorie foods. The diet that triggers overweight is consuming large portions of food, eating foods high in energy, high in fat, high in simple carbohydrates and low in fiber. Physical activity is a risk factor for obesity, where teenagers with light activity are more at risk of becoming obese. In 2018 basic health research, the incidence of overweight was 7.8%. Jambi City Health Service with the number of overweight cases in Jambi City, namely 174 cases. The aim of this study was to determine the relationship between eating patterns and physical activity with the incidence of overweight in adolescents at SMAN 8 Jambi City. The design of this research is quantitative with a cross sectional approach. This research was carried out at SMAN 8 Jambi City in February-June 2023. The population in this research was 359 students of SMAN 8 Jambi City. The sample consisted of 79 respondents. The sampling technique is proportional sampling. The data analysis used is univariate and bivariate analysis using the Chi-Square statistical test. The research results showed a relationship between eating patterns and the incidence of overweight in adolescents (0.000), and the relationship between physical activity and the incidence of overweight in adolescents (0.020). The conclusion is that there is a relationship between eating patterns and physical activity with the incidence of overweight in adolescents at SMAN 8 Jambi City.